2010
DOI: 10.1111/j.1549-8719.2010.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Adenosine A2A and A2B Receptors to Ischemic Coronary Dilation: Role of KV and KATP Channels

Abstract: This study was designed to elucidate the contribution of adenosine A 2A and A 2B receptors to coronary reactive hyperemia and downstream K + channels involved. Coronary blood flow was measured in open-chest anesthetized dogs. Adenosine dose-dependently increased coronary flow from 0.72 ± 0.1 to 2.6 ± 0.5 ml/min/g under control conditions. Inhibition of A 2A receptors with SCH58261 (1 μM) attenuated adenosine-induced dilation by ~50%, while combined administration with the A 2B receptor antagonist alloxazine (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 49 publications
5
71
0
Order By: Relevance
“…Adenosine is well known to play a vasoregulatory role in human coronary arteries (16,17,62,63). We and others (5,63,67,69) have also previously demonstrated the pivotal role of A 2A ARs in CF regulation. We also have preliminary data showing the involvement of A 2 ARs in coronary reactive hyperemia that indirectly supports a physiological role for adenosine in CF regulation (data not shown), which is in support of previous in vivo and ex vivo reactive hyperemia studies (5,12,77).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Adenosine is well known to play a vasoregulatory role in human coronary arteries (16,17,62,63). We and others (5,63,67,69) have also previously demonstrated the pivotal role of A 2A ARs in CF regulation. We also have preliminary data showing the involvement of A 2 ARs in coronary reactive hyperemia that indirectly supports a physiological role for adenosine in CF regulation (data not shown), which is in support of previous in vivo and ex vivo reactive hyperemia studies (5,12,77).…”
Section: Discussionsupporting
confidence: 55%
“…We and others (5,63,67,69) have also previously demonstrated the pivotal role of A 2A ARs in CF regulation. We also have preliminary data showing the involvement of A 2 ARs in coronary reactive hyperemia that indirectly supports a physiological role for adenosine in CF regulation (data not shown), which is in support of previous in vivo and ex vivo reactive hyperemia studies (5,12,77). Additionally, it has been suggested that A 2A AR activation contributes to basal tone in the coronary circulation through the release of nitric oxide (69).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, the application of exogenous adenosine to increase coronary flow for the investigation of adenosine receptor-mediated signaling pathways has been well established [37,44]. Thus, in agreement with previous studies from our laboratory [37,44,49] and others [14], adenosine produced a large increase in coronary flow in isolated mouse hearts, supporting the overall effect of vasodilation by adenosine in the coronary circulation [14,15,37,50,51].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Psupporting
confidence: 78%
“…113,114 Adenosine plays a role in myocardial ischemia as well, which effect is thought to take place through activation of the A2 adenosine receptor, generating in its turn, under ischemic conditions, redistribution of local blood flow from sub-epicardial towards epicardial tissues. 115 So, the moment the critical balance between myocardial oxygen supply and demand is deferred, by either improving supply, or through a reduction in demand, a cascade of chemical reactions take place. It is conceivable that electrical neuromodulation employs its effect through interference with local adenosine handling.…”
Section: Electrical Neuromodulation and Myocardial Ischemiamentioning
confidence: 99%